Production of a Synthetic Material using Cuttlebone and Investigation of its Effect on the Viability and Proliferation of Gingival Fibroblast Cells : Production of a synthetic material using cuttlebone - Akbariforoud, Sima; Shahsavari, Fatemeh; Zand Karimi, Majid; Naddafpour, Nima (Journal of Dental School, 2023)
Objectives Treating and accelerating the healing of oral ulcers caused by various surgeries or injuries have long been important to avoid financial loss and mental harm. Fibroblasts play an important role in wound healing. The current study aimed to produce a suitable synthetic material using cuttlebone and investigate its effect on gum fibroblast cells to help accelerate the healing of oral ulcers. Methods Chitin powder was extracted from squid bone (cuttlebone) to produce a synthetic material, which was subjected to physicochemical control tests. To make the samples, human gingival fibroblasts were cultured in a suitable medium and divided into four groups, namely chitin, gel, base (without active ingredient), and control groups. The effects of the produced synthetic material on the viability and proliferation of gingival fibroblast cells were investigated using MTT assay for 24, 48, and 120 hours. Data were analyzed using Dunnett's post-hoc test, Tukey's test, and one-way analysis of variance (ANOVA). Results About 1.7 grams of chitin powder was obtained from 5 grams of cuttlebone powder. FTIR was used to identify chitin. A gel containing 1% chitin was selected. The results of MTT assay showed that the formulated gel had no toxicity, and the proliferation in chitin and gel groups increased over time compared to the control and base groups. Conclusion It seems that using cuttlebone chitin to make a suitable gel-based synthetic material can accelerate the healing process of mouth ulcers.